Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1175/jhm-d-14-0185.1
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Rivers and Rainfall during NASA’s Iowa Flood Studies (IFloodS) Campaign*

Abstract: Atmospheric rivers (ARs) play a major role in causing extreme precipitation and flooding over the central United States (e.g., Midwest floods of 1993 and 2008). The goal of this study is to characterize rainfall associated with ARs over this region during the Iowa Flood Studies (IFloodS) campaign that took place in April–June 2013. Total precipitation during IFloodS was among the five largest accumulations recorded since the mid-twentieth century over most of this region, with three of the heavy rainfall event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 44 publications
3
36
0
Order By: Relevance
“…To the best of our knowledge, only Nayak et al (2016) provide preliminary insights on the distribution of rainfall during ARs over the central United States, even though the results are limited to a very small sample sizea study period of 66 days in April-June 2013 in which only three ARs occurred. The lack of knowledge regarding the rainfall distribution in ARs is a major gap in the understanding of the science of ARs.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…To the best of our knowledge, only Nayak et al (2016) provide preliminary insights on the distribution of rainfall during ARs over the central United States, even though the results are limited to a very small sample sizea study period of 66 days in April-June 2013 in which only three ARs occurred. The lack of knowledge regarding the rainfall distribution in ARs is a major gap in the understanding of the science of ARs.…”
Section: Introductionmentioning
confidence: 95%
“…Lavers and Villarini (2013) showed that more than 60% of the annual maximum floods during 1979-2011 period were associated with ARs over much of the central United States, with seven out of the ten largest floods associated with these storms. Moreover, ARs are the mechanisms responsible for some of the most devastating flooding events over this region in recent decades, including the floods of July 1993 (Dirmeyer and Kinter, 2009), June 2008 floods over eastern Iowa (Budikova et al, 2010;Smith et al, 2013), May 2010 flood in Nashville (Tennessee) and surrounding areas (Moore et al, 2012), and the flood of April 2013 over Chicago and eastern Iowa (Campos and Wang, 2015;Nayak et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, however, attention has been placed on atmospheric rivers [e.g., Newell et al 1992; Cooperative Institute for Research in the Atmosphere (CIRA) 2016)] and how these elongated corridors of strong water vapor transport influence excessive rain and snowfall production across coastal and mountainous areas of the western United States (e.g., Zhu and Newell 1998;Neiman et al 2002;Ralph et al 2004;Dacre et al 2015;Cordeira et al 2017). Despite this recent interest, only limited discussion has occurred on the influence these atmospheric rivers have on heavy precipitation production outside of areas along the West Coast, especially for locations far removed from the original moisture source regions (Moore et al 2012;Lavers and Villarini 2013;Nayak et al 2016). In fact, Mahoney et al (2016) briefly addressed geographical differences by discussing how southeastern United States heavy rain events often differ from traditional West Coast atmospheric river cases-noting how the former events may experience moisture advection from multiple source regions.…”
mentioning
confidence: 99%